Death Drive: A Psychological Study of Thanatos In Albee’s The Zoo Story - Muhammad, Shang Jamal; Arif, Kawan Othman (Sulaimani Journal for Humanities, 2019)
This paper entitled “Death Drive: A Psychological Study of Thanatos in Albee’s The Zoo Story”, studies the reflections of the despair that the playwrights of the Theatre of the Absurd, particularly Edward Albee, saw in people’s life and behavior after the world wars. As a result of witnessing all the destruction that resulted from the war and the inauthentic nature of modern life, some people lived their life with no aim and no purpose. They started to turn into materialistic objects with no emotions, and do inhuman actions dominated by Thanatos, expressed through self-destructive acts such as suicide and murder. This study claims that Thanatos dominates the life of the characters in The Zoo Story. This is done through a psychological analysis of the play, conducted in two sections. First, there is an introduction which presents Albee’s play through a number of critics’ viewpoints as well as a brief presentation of Thanatos from the psychological perspective. Then, in the second section, there is a psychological study of Thanatos in The Zoo Story.
Keywords: Thanatos; Edward Albee; The Zoo Story; Suicide; Kill; Isolation; Alienation